آراء العاملين في المكتبات نحو استخدام تكنولوجيا المعلومات (الحاسبات والانترنت) دراسة ميدانية في المكتبات التابعة لمديرية الثقافة في محافظة طرطوس - برهوم أديب; سليمان نبيلة; حسن علا (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The research aims to identify the views of the workers of the Directorate of Culture libraries in Tartous towards the use of information technology (computers and the Internet), and to achieve the objectives of the research questionnaire was developed and distributed to a sample of workers in libraries, and using appropriate statistical tests of the most important results: 1- Workers in cultural libraries believes that the use of information technology develops the work of libraries, which is necessary in indexing and retrieval, and organizing groups, and eliminates the role of workers, which is at the same time does not lead to the reluctance of workers, as it does not impede the work of the beneficiaries, and is essential in organizing the loan. 2- characterized the views of workers in the cultural libraries towards the use of information technology (computers and the Internet) positive nature of the increase in years of practical experience in the field of computer, high academic qualification, and follow training courses in the field of IT. يهدف البحث إلى التعرف على آراء العاملين في المكتبات التابعة لمديرية الثقافة في محافظة طرطوس نحو استخدام تكنولوجيا المعلومات (الحاسبات والانترنت), ولتحقيق أهداف البحث تمّ تطوير استبانة وتوزيعها على عينة من العاملين في المكتبات, وباستخدام الاختبارات الإحصائية المناسبة كان من أهم نتائج البحث: 1- يرى العاملون في المكتبات الثقافية بأنّ استخدام تكنولوجيا المعلومات يطوّر عمل المكتبات, وهو ضروري في الفهرسة والاسترجاع, وتنظيم المجموعات, وهو في الوقت نفسه لا يؤدي إلى تلكؤ العاملين, كما أنه لا يعرقل عمل المستفيدين, وضروري في تنظيم الإعارة. 2- تميل آراء العاملين في المكتبات الثقافية نحو استخدام تكنولوجيا المعلومات (الحاسبات والانترنت) بطابع إيجابي بازدياد سنوات الخبرة العملية في مجال المكتبات, وارتفاع المؤهل العلمي, واتباع الدورات التدريبية في مجال المعلوماتية.